2002
DOI: 10.1002/ptr.834
|View full text |Cite
|
Sign up to set email alerts
|

Tea pigments inhibit the production of type 1 (TH1) and type 2 (TH2) helper T cell cytokines in CD4+ T cells

Abstract: Tea pigments are oxidized products of polyphenols derived from tea leaves (Camellia sinensis). Theaflavins are constituents of tea pigments with antioxidant, antineoplastic and antiinflammatory properties similar to their parent compounds. The biological properties of polyphenols and theaflavins have been linked to their capacity to inhibit the activation of nuclear factor-kappaB (NF-kappaB), a transcription factor, which is critically involved in the molecular regulation of a number of proinflammatory cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…The inhibition of NF-nB mRNA transcription by Vimang may likewise be attributable to its constituent polyphenols. It has been shown that various plant polyphenols may inhibit the production of proinflammatory cytokines by inhibiting NF-nB expression [48] and/or by suppressing NF-nB activation through degradation of InB [49] or prevention of NFnB translocation to the nucleus [50]. For example, green tea extracts that contain polyphenolic free radical scavengers such as MA [25] block NF-nB and TNF-a mRNA and protein expression [51].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of NF-nB mRNA transcription by Vimang may likewise be attributable to its constituent polyphenols. It has been shown that various plant polyphenols may inhibit the production of proinflammatory cytokines by inhibiting NF-nB expression [48] and/or by suppressing NF-nB activation through degradation of InB [49] or prevention of NFnB translocation to the nucleus [50]. For example, green tea extracts that contain polyphenolic free radical scavengers such as MA [25] block NF-nB and TNF-a mRNA and protein expression [51].…”
Section: Discussionmentioning
confidence: 99%
“…Transcription of most genes for inflammatory proteins, such as TNFa, IL2, IL9, GM-CSF, iNOS, COX2, is regulated by NFjB [56]. NFjB is the key inducer of cytokine production in T H cells [57].…”
Section: Redox Modulation Of Inflammatory Pathways-nrf2 and Nfjb In Imentioning
confidence: 99%
“…This means that the susceptibility to disease in each of these individuals will also vary depending upon nutrient intakes that alter expression of genetic information. Some examples of other nutrient and non-nutrient environmental factors affecting the T2DM phenotype are energy intake and balance (reviewed in [31]), sleep patterns ( [32,33]), physical activity [34][35][36][37][38], liquid intake [39], and psychological factors, such as stress [40]. Aging and the changes induced by aging, produce health and chronic diseases that are not discrete, dichotomous states, but rather are a continuum.…”
Section: T2dm Qtls In Humansmentioning
confidence: 99%